2002
DOI: 10.1161/hs0102.101625
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Trait Anger and Incident Stroke Risk

Abstract: Background and Purpose-This study examined the relation between trait anger and incident stroke risk among participants without a history of stroke at the first follow-up examination of the Atherosclerosis Risk in Communities (ARIC) study. Methods-The study sample included 13 851 black and white men and women, aged 48 to 67 years, who completed the Spielberger Trait Anger Scale. Median follow-up time was 77.3 months. Results-In the full cohort, Cox proportional hazards regression analyses showed a modest incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…19,20 A high trait anger level has also been shown to be associated with increased risk of stroke in persons younger than 60 years. 21 Still further, anger and hostility have been shown to predict the development of atrial fi brillation in the Framingham Offspring Study. 22 Symptoms of anxiety and depression in the National Health and Nutrition Examination Survey follow-up study 23 and hostility and depressive symptoms in the Coronary Artery Risk Development in Young Adults were shown to be associated with incident hypertension in previously normotensive persons.…”
Section: P Sychos O Cia L Fac Tor S a Nd He A R T Dise A Sementioning
confidence: 97%
See 3 more Smart Citations
“…19,20 A high trait anger level has also been shown to be associated with increased risk of stroke in persons younger than 60 years. 21 Still further, anger and hostility have been shown to predict the development of atrial fi brillation in the Framingham Offspring Study. 22 Symptoms of anxiety and depression in the National Health and Nutrition Examination Survey follow-up study 23 and hostility and depressive symptoms in the Coronary Artery Risk Development in Young Adults were shown to be associated with incident hypertension in previously normotensive persons.…”
Section: P Sychos O Cia L Fac Tor S a Nd He A R T Dise A Sementioning
confidence: 97%
“…21,22,26 The Lubben Social Network score was not included in the models as it was not associated with either outcome. We stratifi ed by sex because previous studies using this anger scale have shown differences between men and women.…”
Section: 26mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Apathy is one of the most common neuropsychiatric symptoms present in 3.2% of the general population, 14.7% of subjects with mild cognitive impairment and 35.9% of subjects with dementia. 6 Multiple lacunes and leukoaraiosis cause various neuropsychiatric symptoms [7][8][9][10] as well as cognitive impairment. [11][12][13] According to the vascular depression hypothesis, small vessel diseases such as silent brain infarction (that is, subcortical lacunes) and/or white matter lesions (WMLs) may disrupt frontal-subcortical circuits and generate depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%